Clinical Evaluation of Corrosion Resistance, Ion Release, and Biocompatibility of CoCr Alloy for Metal-Ceramic Restorations Produced by CAD/CAM Technologies - Zlatina Tomova; Angelina Vlahova; Stefan Zlatev; Ilyana Stoeva; Desislav Tomov; Delyana Davcheva; Viktor Hadzhigaev (MDPI AG, 2023)
Background. CAD/CAM technologies facilitate using powder CoCr alloys to produce metal-ceramic dental restorations. However, base alloys may induce oxidative stress in the oral cavity due to corrosion and ion release. This study evaluated resistance to corrosion and release of metal ions from 3D printed CoCr dental alloy and their effect on oral oxidative stress. Methods. Metal-ceramic crowns with 3D printed copings from CoCr alloy EOS CobaltChrome SP2 (EOS, Germany) were fabricated for 35 patients. Inductively coupled plasma mass spectrometry (ICP-MS) was used for measuring the concentration of Co and Cr ions in non-stimulated saliva before prosthetic treatment (BPT), at 2 h and 7 days after the dental treatment (APT2, APT7, respectively). Open circuit potentials (Eocp) were evaluated at APT2 and APT7. Estimating oral oxidative stress, measurements of 8-isoprostaglandin F2-alpha were conducted using liquid chromatography-tandem mass spectrometry (LC-MS/MS) at stages BPT, APT2, and APT7. Results. Salivary Co level increased at APT2 and decreased to the initial levels at APT7. No statistical difference was found between the levels of 8-isoPGF2-alpha measured, and between the Eocp measurements at APT2 and APT7. Conclusions. The studied alloy showed stable corrosion resistance and the metal ion release did not induce oral oxidative stress.